Blended Learning Model as an Innovative Approach to Enhancing Educational Outcomes - Afia Milza Nawwara (Journal of Education Innovation and Curriculum Development, 2024)
This research explores the implementation of the blended learning model as an innovative approach in modern education. Blended learning, which integrates face-to-face instruction with online learning components, is gaining significant attention for its ability to enhance student engagement, accommodate diverse learning styles, and improve overall learning outcomes. The study aims to examine the benefits, challenges, and effectiveness of blended learning, using a qualitative-descriptive methodology involving literature analysis and field observations. The results reveal that blended learning provides greater flexibility, fosters independent learning, and supports technological skill development among students. However, it also faces limitations such as unequal access to digital tools, a lack of digital literacy, and the need for effective instructional design. Comparisons with previous research confirm the model’s potential while highlighting the importance of infrastructure and teacher readiness. This study concludes that, despite its challenges, the blended learning model represents a viable and transformative solution for addressing the evolving needs of education in the digital age.